STRATEGIC DECISIONS FOR ADVERTISING PLANNING - Ryzhyi, I.B.; Hovera, O.I. (The actual problems of regional economy development, 2019)
The paper deals with the important issues of advertising planning in modern conditions. In particular, the category of non-regular consumers of a certain brand is analyzed. It is noted that this is an extreme area of the target audience. Buyers of this group consume products of this trademark and of competing brands as well. If you increase the frequency of purchases by these consumers, you can increase the sales volume of products. It is substantiated that in order to determine the sales potential of each of the selected types of consumers it is necessary to know their level of awareness about the product category, attitude to it and to a specific trademark, possible types of behavior when buying goods. For this purpose we explore the category of the profile as a generalized description of the personality and lifestyle of a typical target audience representative. The concept of advertising leverage is defined as the ratio of expected sales growth in value terms to the estimation of advertising activities that could cause such growth. It is noted that the advertising leverage is influenced by the life cycle of a product. It has been shown that new buyers are characterized by a decrease in advertising leverage in line with the consistent change in the product life cycle stages. This is due to the fact that the cost to persuade consumers to try a new product for them is high enough, although this type of consumers has high sales potential It determines the basic approaches to the analysis of the target audience, explains methods of work with non-constant consumers of the goods, analyzes the concept of an advertising lever. Based on the Rossiter-Percy grid strategic approaches are proposed to form the consumer's attitude towards the brand. It's been offered a number of strategic approaches to advertising planning related to the formation of consumer motivation, peculiarities of their perception of information about the main benefits of the goods presented in advertising. The article states that in order to determine the sales potential of each type of consumer, namely: a new user of a trademark, a consumer loyal to a particular brand, a non-permanent consumer of a brand, a non-permanent consumer of other brands, a consumer loyal to other brands, you need to know their level awareness of the product category, attitude to it and to a specific brand, possible types of behavior when buying goods. That is why the target audience should be characterized in terms of demographic, geographical, psychographic profiles. The authors of the article argue that it is desirable to involve creative personnel in making more informed strategic decisions when choosing advertising means. If creative and media decisions are made by a professional team, then the effectiveness of advertising efforts will be higher. The authors of the article also note that the geographical factor greatly complicates the work of advertising planning professionals. Because in different geographical areas consumer preferences differ, even in one region there may be different attitude to trademarks and advertising. These features should be taken into account when designing your advertising plan.